Interlaminar differences in the pyramidal cell phenotype in parietal cortex of an Indian bat, cynopterus sphinx - Srivastava, U. C.; Pathak, S. V. (Cellular and Molecular Biology, 2010)
To study interlaminar phenotypic variations in the pyramidal neurons of parietal isocortex in bat (Cynopterus sphinx), Golgi and Nissl methods have been employed. The parietal isocortex is relatively thin in the bat as compared to prototheria with layer III, V and VI accounting for more than two-thirds of total cortical thickness. Thick cell free layer I and thinnest accentuated layer II are quite in connotation with other chiropterids. Poor demarcation of layer III/IV in the present study is also in connotation with primitive eutherian mammal (i.e. prototherian) and other chiropterids. Most of the pyramidal cells in the different layers of the parietal isocortex are of typical type as seen in other eutherians but differ significantly in terms of soma shape and size, extent of dendritic arbor, diameter of dendrites and spine density. Percentage of pyramidal neurons, diameter of apical dendrite and spine density on apical dendrite appear to follow an increasing trend from primitive to advanced mammals; but extent of dendrites are probably governed by the specific life patterns of these mammals. It is thus concluded that ‘typical' pyramidal neurons in parietal isocortex are similar in therians but different from those in prototherians. It is possible that these cells might have arisen among early eutherians after divergence from prototherian stock.